Composition, mixture for solid battery, sulfide solid electrolyte layer, electrode layer, and secondary battery

JP2025036343AActive Publication Date: 2025-03-14DAIKIN INDUSTRIES LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024147730
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-29
Publication Date
2025-03-14
Estimated Expiration
2044-08-29

AI Technical Summary

Benefits of technology

【0031】 本開示によれば、硫化物固体電解質を有する電気化学デバイスの抵抗を低減可能な組成物、固体電池用合剤、硫化物固体電解質層、電極層、及び、二次電池を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036343000001
    Figure 2025036343000001
  • Figure 2025036343000002
    Figure 2025036343000002
  • Figure 2025036343000003
    Figure 2025036343000003
Patent Text Reader

Abstract

To provide a composition capable of reducing resistance of an electrochemical device having a sulfide solid electrolyte, a mixture for a solid battery, a sulfide solid electrolyte layer, an electrode layer, and a secondary battery.SOLUTION: A composition contains at least one of fluoropolyether represented by any one of the following formulae (1) to (3), and a sulfide solid electrolyte. Formula (1): R1-O-Ra1-Rb1-O-Ra1-R1. Formula (2): R2-Rb2-O-Ra2-Rb2-R2, and formula (3): R3-Rb3-O-Ra3-R3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composition, a mixture for a solid state battery, a sulfide solid electrolyte layer, an electrode layer, and a secondary battery. [Background technology]

[0002] 2. Description of the Related Art With the trend toward lighter and smaller electric appliances in recent years, the development of electrochemical devices having high energy density, such as lithium ion secondary batteries, has progressed.

[0003] As technologies relating to electrochemical devices, Patent Document 1 discloses a solid electrolyte composition containing a specific (per)fluoropolyether, a specific poly(alkylene) oxide, and a lithium salt, and Patent Document 2 discloses a solid electrolyte slurry containing an inorganic solid electrolyte material, and a liquid such as perfluoropolyether and silicone oil, and in which the content of a binder resin is adjusted to a specific range. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2022-506854 [Patent Document 2] JP 2016-062709 A Summary of the Invention [Problem to be solved by the invention]

[0005] When manufacturing an electrochemical device such as a secondary battery, it is believed that the resistance of the electrodes and the like is reduced by pressing the electrodes and the like at high pressure. In particular, when manufacturing an electrochemical device having a sulfide solid electrolyte, it is believed that the effect of reducing the resistance by high pressure pressing is remarkable. On the other hand, in order to simplify the manufacturing process of the electrochemical device and reduce the manufacturing cost, it is required to press the electrodes and the like at low pressure. However, when a low pressure press is used in manufacturing an electrochemical device having a sulfide solid electrolyte, the above-mentioned effect of reducing the resistance tends to be difficult to obtain. Therefore, a new technology is needed to reduce the resistance of an electrochemical device having a sulfide solid electrolyte.

[0006] An object of the present disclosure is to solve the above problems and to provide a composition capable of reducing the resistance of an electrochemical device having a sulfide solid electrolyte, a mixture for a solid battery, a sulfide solid electrolyte layer, an electrode layer, and a secondary battery. [Means for solving the problem]

[0007] The present disclosure (1) relates to a polymerizable composition comprising at least one fluoropolyether represented by any one of the following formulas (1) to (3): and a sulfide solid electrolyte. (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (In the formula, Ra 1 ~Ra 3 each independently represents a group containing a fluorine-free alkylene unit and / or a fluorine-free oxyalkylene unit, Ra 1 ~Ra 3Each oxyalkylene unit is independently -CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 3 are each independently a fluoropolyether group represented by the following formula (4): R 1 ~R 3 are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0008] The present disclosure (2) relates to the Ra 1 ~Ra 3 are each independently a polyoxyalkylene group represented by the following formula (Ra-I): (Ra-I): -(CH 2 CH 2 O)r(CH 2 CH(CH 3 )O)s(CH 2 CH(CH 2 CH 3 )O)t(CH 2 CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

[0009] This disclosure (3) relates to the Ra 1 ~Ra 3The composition according to the present disclosure (1) or (2), wherein the number average molecular weight is 40 to 4,000.

[0010] The present disclosure (4) is the composition according to any one of the present disclosures (1) to (3), in which the Rfs are each independently a fluoropolyether group represented by the following formula (Rf-I): Formula (Rf-I): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 Rc 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeat unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e, and f is 1 or greater.

[0011] The present disclosure (5) is the composition according to any one of the present disclosures (1) to (4), in which the Rfs are each independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary.

[0012] The present disclosure (6) is the composition according to the present disclosure (5), wherein each Rf is independently a group represented by the formula (Rf-I-II).

[0013] This disclosure (7) relates to the R 1 ~R 3 is the composition according to any one of the present disclosures (1) to (6), wherein each of

[0014] The present disclosure (8) is directed to a sulfide solid electrolyte, 2 SP 2 S 5 The composition according to any one of the present disclosures (1) to (7),

[0015] The present disclosure (9) is the composition according to any one of the present disclosures (1) to (8), which contains an alkali metal salt.

[0016] The present disclosure (10) is the composition according to the present disclosure (9), wherein the alkali metal salt is lithium bis(trifluoromethanesulfonimide).

[0017] The present disclosure (11) is the composition according to any one of the present disclosures (1) to (10), wherein the fluoropolyether is liquid at any temperature between 25°C and 80°C.

[0018] The present disclosure (12) is the composition according to any one of the present disclosures (1) to (11), in which the content of the polyalkylene oxide represented by the following formula (5) is less than 20 mass %. (5)R 1B -(OCHR 1A (CH 2 )jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is an integer of 0 or 1 to 2, R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

[0019] The present disclosure (13) is a mixture for a solid battery, comprising the composition according to any one of the present disclosures (1) to (12).

[0020] The present disclosure (14) is a mixture for a solid-state battery according to the present disclosure (13), which contains a binder.

[0021] The present disclosure (15) is a mixture for a solid battery according to the present disclosure (13) or (14), which contains a conductive assistant.

[0022] The present disclosure (16) is a sulfide solid electrolyte layer using the mixture for a solid battery according to any one of the present disclosures (13) to (15).

[0023] The present disclosure (17) is an electrode layer using the mixture for a solid battery according to any one of the present disclosures (13) to (15).

[0024] The present disclosure (18) is a secondary battery including the sulfide solid electrolyte layer according to the present disclosure (16) and the electrode layer according to the present disclosure (17).

[0025] The present disclosure (19) is a secondary battery including the sulfide solid electrolyte layer according to the present disclosure (16).

[0026] The present disclosure (20) is a secondary battery including the electrode layer according to the present disclosure (17).

[0027] The present disclosure (21) is a semiconductor device in which the electrode layer has an active material layer, In the secondary battery according to the present disclosure (18), the content of the fluoropolyether in the active material layer is 1 to 25% by volume.

[0028] The present disclosure (22) is a semiconductor device in which the electrode layer has an active material layer, In the secondary battery according to the present disclosure (20), the content of the fluoropolyether in the active material layer is 1 to 25% by volume.

[0029] The present disclosure (23) is the secondary battery according to the present disclosure (21), wherein the content of the fluoropolyether in the active material layer is 1 to 10% by volume.

[0030] The present disclosure (24) is the secondary battery according to the present disclosure (22), wherein the content of the fluoropolyether in the active material layer is 1 to 10% by volume. Effect of the Invention

[0031] According to the present disclosure, it is possible to provide a composition capable of reducing the resistance of an electrochemical device having a sulfide solid electrolyte, a mixture for a solid battery, a sulfide solid electrolyte layer, an electrode layer, and a secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The present disclosure will now be described in detail.

[0033] <Composition> The present disclosure relates to a composition containing at least one fluoropolyether represented by any one of the following formulas (1) to (3) and a sulfide solid electrolyte. (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (In the formula, Ra 1 ~Ra 3 each independently represents a group containing a fluorine-free alkylene unit and / or a fluorine-free oxyalkylene unit, Ra 1 ~Ra 3 Each oxyalkylene unit is independently -CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 3 are each independently a fluoropolyether group represented by the following formula (4): R 1 ~R 3 are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0034] Since the composition of the present disclosure has the above-mentioned configuration, it is possible to reduce the resistance of an electrochemical device having a sulfide solid electrolyte. In addition, while in conventional methods, the resistance tends to increase when the pressing pressure of electrodes, etc. is reduced, the composition of the present disclosure can suppress the increase in resistance when the pressing pressure is reduced.

[0035] Ra 1 ~Ra 3 The alkylene unit may be linear or branched, but is preferably linear, and preferably has 1 to 3 carbon atoms.

[0036] Ra 1 ~Ra 3 The oxyalkylene unit is -CH 2 In the case of CH(J)O-, the alkyl group of J may be linear or branched, but is preferably linear. The alkyl group of J preferably has 1 to 3 carbon atoms. Examples of the aryl group represented by J include a phenyl group, a 4-nitrophenyl group, a 4-acetylaminophenyl group, and a 4-methanesulfonylphenyl group.

[0037] Ra 1 ~Ra 3 In the formula (I), the number of fluorine-free alkylene units and fluorine-free oxyalkylene units is preferably 4 to 50 in total.

[0038] Ra 1 ~Ra 3 Each of the groups preferably independently contains at least an oxyalkylene unit, and is more preferably a polyoxyalkylene group represented by the following formula (Ra-I). (Ra-I): -(CH 2 CH 2 O)r-(CH 2 CH(CH 3 )O)s-(CH 2 CH(CH 2 CH 3 )O)t-(CH 2 CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

[0039] In the above formula (Ra-I), r is preferably 1 or more, more preferably 2 or more, and is preferably 30 or less, more preferably 20 or less. s, t and u are preferably 10 or less, more preferably 5 or less, and further preferably 0. r+s+t+u is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.

[0040] Ra 1 ~Ra 3 The number average molecular weight of is preferably 40 or more, more preferably 100 or more, and is preferably 4000 or less, more preferably 1000 or less. In the present specification, Ra 1 ~Ra 3 The number average molecular weight of 1 This is a value measured by H-NMR.

[0041] Rb 1 ~Rb 3 In the above formula (4), Rf 1 and Rf 2 The alkylene group may be linear or branched, but is preferably linear. Rf 1 and Rf 2 The alkylene group is preferably a fluorine-substituted alkylene group substituted with a fluorine atom. Rf 1 and Rf 2 The alkylene group preferably has 1 to 3 carbon atoms.

[0042] Rb 1 ~Rb 3 In the above formula (4), Rf may have a ring structure.

[0043] Rb 1 ~Rb 3 In the above formula (4), Rf is preferably a fluoropolyether group represented by the following formula (Rf-I). Formula (Rf-I): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 Rc 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeat unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e, and f is 1 or greater.

[0044] Rc is preferably a hydrogen atom or a fluorine atom, and more preferably a fluorine atom, That is, Rf in the formula (4) is preferably a perfluoropolyether group.

[0045] It is preferable that a, b, c, d, e and f each independently represent an integer of 0 to 100.

[0046] The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, and may be 15 or more or 20 or more. The sum of a, b, c, d, e and f is preferably 100 or less, more preferably 60 or less, and may be 50 or less or 30 or less.

[0047] Each repeat unit denoted by a, b, c, d, e, or f may be linear or branched. -(OC 6 F 12 )- is, for example, -(OCF 2 CF 2 CF 2 CF2 CF 2 CF 2 )-, -(OCF(CF 3 )CF 2 CF 2 CF 2 CF 2 )-, -(OCF 2 CF(CF 3 )CF 2 CF 2 CF 2 )-, -(OCF 2 CF 2 CF(CF 3 )CF 2 CF 2 )-, -(OCF 2 CF 2 CF 2 CF(CF 3 )CF 2 )-, -(OCF 2 CF 2 CF 2 CF 2 CF(CF 3 ))-. -(OC 5 F 10 )- is, for example, -(OCF 2 CF 2 CF 2 CF 2 CF 2 )-, -(OCF(CF 3 )CF 2 CF 2 CF 2 )-, -(OCF 2 CF(CF 3 )CF 2 CF 2 )-, -(OCF 2 CF 2 CF(CF 3 )CF 2 )-, -(OCF 2 CF 2 CF 2 CF(CF 3 ))- may be either. -(OC 4 F 8 )- is, for example, -(OCF 2 CF 2 CF2 CF 2 )-, -(OCF(CF 3 )CF 2 CF 2 )-, -(OCF 2 CF(CF 3 )CF 2 )-, -(OCF 2 CF 2 CF(CF 3 ))-, -(OC(CF 3 ) 2 CF 2 )-, -(OCF 2 C(CF 3 ) 2 )-, -(OCF(CF 3 )CF(CF 3 ))-, -(OCF(C 2 F 5 )CF 2 )-, -(OCF 2 CF(C 2 F 5 ))-. -(OC 3 F 6 )-(i.e., in the above formula (Rf-I), all Rc are fluorine atoms) is, for example, -(OCF 2 CF 2 CF 2 )-, -(OCF(CF 3 )CF 2 )-, -(OCF 2 CF(CF 3 ))-. -(OC 2 F 4 )- is, for example, -(OCF 2 CF 2 )-, -(OCF(CF 3 ))-.

[0048] Rf may be a group represented by any one of the following formulas (Rf-II) to (Rf-IV). Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary. Formula (Rf-I-III): -(R 20 -R 21 )g- (In the formula, R 20 is OCF 2 Or O.C. 2 F 4 and R 21 is O.C. 2 F 4 , O.C. 3 F 6 , O.C. 4 F 8 , O.C. 5 F 10 and O.C. 6 F 12 or a combination of two or three groups selected from these groups, g is an integer from 2 to 100. Formula (Rf-I-IV): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, e is an integer of 1 to 200, a, b, c, d, and f each independently represent an integer of 0 to 200; The order of each repeating unit with a, b, c, d, e, or f is arbitrary. Formula (Rf-IV): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, f is an integer of 1 to 200, a, b, c, d, and e each independently represent an integer of 0 to 200; The order of each repeating unit with a, b, c, d, e, or f is arbitrary.

[0049] In the above formula (Rf-II), d is preferably 5 to 200, more preferably 10 to 100, and further preferably 15 to 50, and may be 25 to 35. The above formula (Rf-II) is preferably -(OCF 2 CF 2 CF 2 )d- or -(OCF(CF 3 )CF 2 )d- is a group represented by the formula:

[0050] In the above formula (Rf-I-II), e and f are each independently an integer of preferably 5 to 200, more preferably 10 to 200. The sum of c, d, e and f is preferably 5 or more, more preferably 10 or more, and may be 15 or more, or 20 or more. The above formula (Rf-I-II) is preferably -(OCF 2 CF 2 CF 2 CF 2 )c-(OCF 2 CF 2CF 2 )d-(OCF 2 CF 2 )e-(OCF 2 )f-, or -(OC 2 F 4 )e-(OCF 2 )f-, and more preferably -(OC 2 F 4 )e-(OCF 2 )f- is a group represented by the formula:

[0051] In the above formula (Rf-I-III), R 20 Preferably, OC 2 F 4 and R 21 Preferably, OC 2 F 4 , O.C. 3 F 6 and O.C. 4 F 8 or a combination of two or three groups independently selected from these groups, more preferably OC 3 F 6 and O.C. 4 F 8 is a group selected from 2 F 4 , O.C. 3 F 6 and O.C. 4 F 8 Examples of the combination of two or three groups independently selected from the group consisting of, but not limited to, -OC 2 F 4 O.C. 3 F 6 -, -OC 2 F 4 O.C. 4 F 8 -, -OC 3 F 6 O.C. 2 F 4 -, -OC 3 F 6 O.C. 3 F 6 -, -OC 3 F 6 O.C. 4 F8 -,-OC4F8OC 4 F 8 -, -OC 4 F 8 O.C. 3 F 6 -, -OC 4 F 8 O.C. 2 F 4 -, -OC 2 F 4 OC2F4OC 3 F 6 -, -OC 2 F 4 O.C. 2 F 4 O.C. 4 F 8 -, -OC 2 F 4 O.C. 3 F 6 OC2F4-, -OC 2 F 4 O.C. 3 F 6 O.C. 3 F 6 -, -OC 2 F 4 O.C. 4 F 8 O.C. 2 F 4 -, -OC 3 F 6 O.C. 2 F 4 O.C. 2 F 4 -, -OC 3 F 6 O.C. 2 F 4 O.C. 3 F 6 -, -OC 3 F 6 OC3F6OC 2 F 4 - and -OC 4 F 8 O.C. 2 F 4 O.C. 2 F 4 --etc. In the above formula (Rf-I-III), g is preferably an integer of 3 or more, more preferably an integer of 5 or more. The above g is preferably an integer of 50 or less. In the above formula (Rf-I-III), OC 2 F 4 , O.C. 3 F 6 , O.C. 4 F 8 , O.C. 5 F 10 , and O.C. 6 F 12 may be either a straight chain or a branched chain, and is preferably a straight chain. In this embodiment, the above formula (Rf-I-III) is preferably -(OC 2 F 4 -OC 3 F 6 )g- or -(OC 2 F 4 -OC 4 F 8 )g-.

[0052] In the above formula (Rf-I-IV), e is preferably an integer of 1 to 100, more preferably an integer of 5 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example, 10 to 100.

[0053] In the above formula (Rf-IV), f is preferably an integer of 1 to 100, more preferably an integer of 5 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example, 10 to 100.

[0054] In Rf, the ratio of e to f (hereinafter referred to as "e / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the e / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the e / f ratio, the more the lubricity is improved. On the other hand, by making the e / f ratio 0.5 or more, the stability of the compound can be further improved. The larger the e / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of the e / f ratio is preferably 0.8 or more.

[0055] Rf is represented by the following formula (Rf-I-VI): -(OCF 2 CF 2 CF 2 )a-(OCF(CF 3 )CF 2 )b-(OCF 2 CF(CF3))c-(OCF 2 CF 2 )d-(OCF(CF 3 ))e-(OCF 2 )f- (In the formula, a, b, c, d, e, and f each independently represent an integer of 0 to 200, the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeating unit with a, b, c, d, e, or f is arbitrary. The group may be represented by the following formula:

[0056] Rf is represented by the following formula (Rf-I-VII): -(OCF 2 CF 2 )d-(OCF(CF 3 ))e-(OCF 2 )f- (In the formula, d, e, and f each independently represent an integer of 0 to 200, the sum of d, e, and f is 1 or more, The order of the repeating units marked with d, e, or f is arbitrary. When Rf is this group, it is considered that the salt solubility becomes better because the number of ether bonds increases and the cations of the salt become more easily coordinated.

[0057] In Rf, the ratio of d to f (hereinafter referred to as "d / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the d / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the d / f ratio, the more the lubricity is improved. On the other hand, by making the d / f ratio 0.5 or more, the stability of the compound can be further improved. The larger the d / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of the d / f ratio is preferably 0.8 or more.

[0058] Each Rf is preferably independently a group represented by the above formula (Rf-II) or (Rf-I-II), and more preferably a group represented by the above formula (Rf-I-II).

[0059] The number average molecular weight of Rf is not particularly limited, but is, for example, 500 to 30,000, preferably 1,500 to 30,000, and more preferably 2,000 to 10,000. In this specification, the number average molecular weight of Rf is 19 This is a value measured by F-NMR.

[0060] R 1 ~R 3 The alkyl group and the fluoroalkyl group may be linear or branched, but are preferably linear. R 1 ~R 3 Examples of the aryl group include a phenyl group, a 4-nitrophenyl group, a 4-acetylaminophenyl group, and a 4-methanesulfonylphenyl group.

[0061] R 1 ~R 3are each independently preferably an alkyl group having 1 to 3 carbon atoms or a fluoroalkyl group having 1 to 3 carbon atoms, more preferably a methyl group, an ethyl group, a trifluoromethyl group or a pentafluoroethyl group, and further preferably a methyl group, a trifluoromethyl group or a pentafluoroethyl group.

[0062] The fluoropolyether is particularly preferably the fluoropolyether represented by the above formula (1) because of its excellent ionic conductivity.

[0063] The above fluoropolyether is preferably liquid at any temperature between 25°C and 80°C, and more preferably liquid at 25°C, because it has good ionic conductivity and the like. Examples of a form that is "liquid at any temperature between 25°C and 80°C" include a form that is solid at 25°C and liquid at 50°C, and a form that is solid at 50°C and liquid at 80°C. A form that is liquid at low temperatures and solid at high temperatures does not usually exist, and therefore is not included in the form that is "liquid at any temperature between 25°C and 80°C".

[0064] In the composition of the present disclosure, the content of the fluoropolyether is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more, and is preferably 25 mass% or less, more preferably 15 mass% or less, and even more preferably 10 mass% or less.

[0065] The sulfide solid electrolyte is not particularly limited, and may be Li 2 SP 2 S 5 , Li 2 SP 2 S 3 , Li 2 SP 2 S 3 -P 2 S 5 , Li 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , LiI-Li 2 SP2 S 5 , LiI-Li 2 SP 2 O 5 , LiI-Li 3 PO 4 -P 2 S 5 , LiI-Li 2 S-SiS 2 -P 2 S 5 , Li 2 S-SiS 2 -Li 4 SiO 4 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 3 P.S. 4 -Li 4 GeS 4 , Li 3.4 P 0.6 S 0.4 S 4 , Li 3.25 P 0.25 Ge 0.76 S 4 , Li 4-x Ge 1-x P x S 4 (x=0.6~0.8), Li 4+y Ge 1-y Ga y S 4 (y=0.2~0.3), LiPSCl, LiCl, Li 7-x-2y P.S. 6-x-y Cl x (0.8≦x≦1.7, 0 <y≦-0.25x+0.5)、Li 10 SnP 2 S 12 , LiI-LiBr-Li 2 SP 2 S 5 Any one selected from the above, or a mixture of two or more of them can be used. Among them, LiI-LiBr-Li 2 SP 2 S 5 is particularly preferred.

[0066] The sulfide solid electrolyte preferably contains lithium. The sulfide solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.

[0067] In the composition of the present disclosure, the content of the sulfide solid electrolyte is preferably 75 mass% or more, more preferably 85 mass% or more, and even more preferably 90 mass% or more, and is preferably 99.9 mass% or less, more preferably 99.5 mass% or less, and even more preferably 99 mass% or less.

[0068] The compositions of the present disclosure may include a fibrillating resin. The fibrillating resin is a resin that easily fibrillates when a shear stress is applied, and examples thereof include liquid crystal polymer (LCP), cellulose, acrylic resin, ultra-high molecular weight polyethylene, polytetrafluoroethylene (PTFE), etc. These may be used alone or in combination of two or more. Among these, PTFE is preferred from the viewpoints of chemical stability, thermal stability, and processability.

[0069] The PTFE may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing a polymerization unit based on TFE (TFE unit) and a polymerization unit based on a modified monomer (hereinafter also referred to as a "modified monomer unit"). The modified PTFE may contain 99.0% by mass or more of TFE units and 1.0% by mass or less of modified monomer units. The modified PTFE may be composed only of TFE units and modified monomer units. As the PTFE, the modified PTFE is preferred in that it improves the binding force, sheet strength and flexibility.

[0070] The modified PTFE preferably has a modified monomer unit content of 0.00001 to 1.0% by mass relative to the total polymerized units, in terms of improving the binding force, sheet strength, and flexibility. The lower limit of the modified monomer unit content is preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and even more preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, and even more preferably 0.30% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0071] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0072] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene [CTFE], perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylenes, etc. The modified monomers used may be one type or multiple types.

[0073] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF 2 =CF-ORff(A) (wherein Rff represents a perfluoro organic group). In this specification, the "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.

[0074] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) [PAVE], where Rff in the general formula (A) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0075] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0076] The perfluorovinyl ether further includes those in which, in the above general formula (A), Rff is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and those in which Rff is the following formula:

[0077] [ka]

[0078] (wherein m represents 0 or an integer of 1 to 4), Rff is a group represented by the following formula:

[0079] [ka]

[0080] (wherein n represents an integer of 1 to 4).

[0081] The (perfluoroalkyl)ethylene [PFAE] is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE] and (perfluorohexyl)ethylene.

[0082] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF 2 =CF-CF 2 -ORff1 (B) (In the formula, Rff 1 represents a perfluoro organic group.

[0083] Rff 1 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. 2 =CF-CF 2 -O-CF 3 , C.F. 2 =CF-CF 2 -OC 2 F 5 , C.F. 2 =CF-CF 2 -OC 3 F 7 , and CF 2 =CF-CF 2 -OC 4 F 9 At least one selected from the group consisting of CF 2 =CF-CF 2 -OC 2 F 5 , C.F. 2 =CF-CF 2 -OC 3 F 7 , and CF 2 =CF-CF 2 -OC 4 F 9 More preferably, at least one selected from the group consisting of CF 2 =CF-CF 2 -O-CF 2 CF 2 CF 3 is more preferred.

[0084] As the modified monomer, from the viewpoint of improving the extensibility, binding strength, and flexibility of the composite sheet, at least one selected from the group consisting of PAVE, HFP, VDF, and CTFE is preferable, and at least one selected from the group consisting of perfluoro(methyl vinyl ether) [PMVE], HFP, VDF, and CTFE is more preferable.

[0085] The PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-T-2005-527652 may be used.

[0086] Examples of PTFE that are commonly available on the market include F-104, F-106, F-107, F-104C, F-121, F-201, F-205, F-208, and F-302 manufactured by Daikin Industries, 60X, 601X, 602X, 605XTX, 613AX, 62X, 62NX, 62XTX, 640XTX, 641XTX, 650XTX, 669X, 669NX, 6CX, 6CNX, CFP6000X, 6J, 6CJ, 62J, 640J, and 641J manufactured by Chemours, and T manufactured by 3M. F2029, TF2025Z, TF2053Z, TF2073Z, TF2001Z, TF2071USZ, TF2072Z, etc., CD145, CD123, CD126E, CD097, CD084E, CD086EL, CD086EH, CD090E, CD122E, CD141E, CD127E, etc., manufactured by AGC, and DF681F, DF680F, DF330F, DF291F, DF230F, DF210F, DF132F, DF130F, DF120F, etc., manufactured by Solvay.

[0087] In terms of being able to form a composite sheet having even greater strength, the PTFE preferably has an endothermic peak temperature of 320° C. or higher, more preferably 325° C. or higher, even more preferably 330° C. or higher, even more preferably 335° C. or higher, even more preferably 340° C. or higher, even more preferably 342° C. or higher, and particularly preferably 344° C. or higher. The endothermic peak temperature is also preferably 350° C. or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on a fluororesin that has not been heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is regarded as the endothermic peak temperature.

[0088] The above-mentioned PTFE preferably has one or more endothermic peaks in the range of 333 to 347°C in a heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC], and has a heat of fusion of 62 mJ / mg or more at 290 to 350°C calculated from the heat of fusion curve.

[0089] In the composition of the present disclosure, the content of the fibrillar resin is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, even more preferably 0.5 mass% or more, even more preferably 1.0 mass% or more, and preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 30 mass% or less, and even more preferably 10 mass% or less.

[0090] In the composition of the present disclosure, the content of the polyalkylene oxide represented by the following formula (5) is preferably less than 20% by mass. This ensures good ionic conductivity. If the content is 20% by mass or more, the viscosity of the composition increases, the ionic conductivity decreases, and the electrochemical stability tends to decrease. (5)R 1B -(OCHR 1A (CH 2 )jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is an integer of 0 or 1 to 2, R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

[0091] In the composition of the present disclosure, the content of the polyalkylene oxide represented by the above formula (5) is more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 1% by mass or less. The lower limit is not particularly limited, and may be 0% by mass.

[0092] The composition of the present disclosure may contain an alkali metal salt, particularly a lithium salt, which improves the conductivity of lithium ions.

[0093] Any lithium salt can be used as the lithium salt, and specific examples include the following: LiPF 6 , LiBF 4 , LiClO 4 , LiAlF 4 , LiSbF 6 , LiTaF 6 , LiWF 7 , LiAsF 6 , LiAlCl 4 , LiI, LiBr, LiCl, LiB 10 Cl 10 , Li 2 SiF 6 , Li 2 PFO 3 , LiPO 2 F 2 Inorganic lithium salts such as; LiWOF 5 Lithium tungstates such as: HCO 2 Li, C.H. 3 CO 2 Li, C.H. 2 FCO 2 Li, C.H.F. 2 CO 2 Li, C.F. 3 CO 2 Li, C.F. 3 CH 2 CO 2 Li, C.F. 3 CF 2 CO 2 Li, C.F. 3 CF 2 CF 2 CO2 Li, C.F. 3 CF 2 CF 2 CF 2 CO 2 Lithium carboxylates such as Li; FSO 3 Li, C.H. 3 SO 3 Li, C.H. 2 FSO 3 Li, C.H.F. 2 SO 3 Li, C.F. 3 SO 3 Li, C.F. 3 CF 2 SO 3 Li, C.F. 3 CF 2 CF 2 SO 3 Li, C.F. 3 CF 2 CF 2 CF 2 SO 3 Li, lithium methyl sulfate, lithium ethyl sulfate (C 2 H 5 OSO 3 Li), lithium salts having an S=O group such as lithium 2,2,2-trifluoroethyl sulfate; Lithium bis(trifluoromethanesulfonimide) (LiTFSI), Lithium bis(monofluorosulfonimide) (LiFSI), LiN(FCO) 2 , LiN(FCO)(FSO 2 ), LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2, lithium bisperfluoroethanesulfonylimide, lithium cyclic 1,2-perfluoroethanedisulfonylimide, lithium cyclic 1,3-perfluoropropanedisulfonylimide, lithium cyclic 1,2-ethanedisulfonylimide, lithium cyclic 1,3-propanedisulfonylimide, lithium cyclic 1,4-perfluorobutanedisulfonylimide, LiN(CF 3 SO 2 )(FSO 2 ), LiN(CF 3 SO 2 )(C 3 F 7 SO 2 ), LiN(CF 3 SO 2 )(C 4 F 9 SO 2 ), LiN(POF 2 ) 2 Lithium imide salts such as; LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 Lithium methide salts such as; Others, Formula: LiPF a (C n F 2n+1 ) 6-a (wherein a is an integer of 0 to 5, and n is an integer of 1 to 6) 3 (C 2 F 5 ) 3 , LiPF 3 (CF 3 ) 3 , LiPF 3 (iso-C 3 F 7 ) 3 , LiPF 5 (iso-C 3 F 7 ), LiPF 4 (CF 3 ) 2 , LiPF 4(C 2 F 5 ) 2 ), LiPF 4 (CF 3 SO 2 ) 2 , LiPF 4 (C 2 F 5 SO 2 ) 2 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiBF 3 C 3 F 7 , LiBF 2 (CF 3 ) 2 , LiBF 2 (C 2 F 5 ) 2 , LiBF 2 (CF 3 SO 2 ) 2 , LiBF 2 (C 2 F 5 SO 2 ) 2 Fluorine-containing organic lithium salts such as LiSCN and LiB(CN) 4 , LiB(C 6 H 5 ) 4 , Li 2 (C 2 O 4 ), LiP(C 2 O 4 ) 3 , Li 2 B 12 F b H 12-b (b is an integer of 0 to 3), etc.

[0094] Among them, LiTFSI, LiFSI, and LiPF 6 , LiBF 4 , LiSbF 6 , LiTaF 6 , LiPO 2 F 2 , FSO 3 Li, C.F.3 SO 3 Li, LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , Lithium cyclic 1,2-perfluoroethane disulfonylimide, Lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiPF 3 (CF 3 ) 3 , LiPF 3 (C 2 F 5 ) 3 LiTFSI, LiFSI, LiPF, etc. are preferred. 6 is particularly preferred.

[0095] These lithium salts may be used alone or in combination of two or more. A preferred example of a combination of two or more is LiPF 6 and LiBF 4 Use in combination with LiPF 6 And LiPO 2 F 2 , C 2 H 5 OSO 3 Li or FSO 3 When used in combination with Li, it has the effect of improving high-temperature storage characteristics, load characteristics, and cycle characteristics.

[0096] Another example is the combined use of an inorganic lithium salt and an organic lithium salt, which has the effect of suppressing deterioration due to high-temperature storage. 3 SO 3 Li, LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , Lithium cyclic 1,2-perfluoroethane disulfonylimide, Lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiPF 3 (CF 3 ) 3 , LiPF 3 (C 2 F 5 ) 3 etc. are preferred.

[0097] In the composition of the present disclosure, the content of the lithium salt relative to the fluoropolyether is preferably 0.1% by mass or more, more preferably 1% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less.

[0098] <Mixture for solid-state batteries> INDUSTRIAL APPLICABILITY The composition of the present disclosure is capable of reducing the resistance of an electrochemical device, and is therefore useful as a mixture for a solid-state battery, which is an electrochemical device. The present disclosure also relates to a solid-state battery mixture comprising the composition of the present disclosure.

[0099] In the solid battery mixture of the present disclosure, the content of the composition of the present disclosure is preferably 70 mass % or more, more preferably 80 mass % or more, even more preferably 85 mass % or more, and preferably 100 mass % or less, even more preferably 95 mass % or less.

[0100] The solid battery mixture of the present disclosure may contain a conductive assistant. The mixture for electrochemical devices according to the present disclosure may contain a conductive assistant. The conductive assistant is not particularly limited, but examples thereof include metal materials such as copper, nickel, and gold, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as vapor grown carbon fiber (VGCF). Among these, carbon materials are preferred, amorphous carbon is more preferred, and VGCF is even more preferred. These may be used alone or in any combination and ratio of two or more.

[0101] In the solid battery mixture of the present disclosure, the content of the conductive assistant is preferably 20 mass % or less, more preferably 15 mass % or less, and further preferably 10 mass % or less. The lower limit is not particularly limited, and may be 0 mass %.

[0102] The solid battery mixture of the present disclosure may contain a binder. The binder is not particularly limited, and examples thereof include resin-based polymers such as the above-mentioned fibrillar resins, polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, chitosan, alginic acid, polyacrylic acid, polyimide, cellulose, and nitrocellulose; rubber-like polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or hydrogenated products thereof; and EPDM (ethylene-propylene Examples of suitable polymers include thermoplastic elastomers such as styrene-ethylene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, and hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride, vinylidene fluoride copolymers, and tetrafluoroethylene-ethylene copolymers; and polymer compositions having ionic conductivity for alkali metal ions (especially lithium ions). These may be used alone or in any combination and ratio of two or more.

[0103] In the mixture for a solid battery of the present disclosure, the content of the binder is usually 0.1 to 10 mass %.

[0104] The solid battery mixture of the present disclosure contains a sulfide solid electrolyte, and therefore can be used as a solid electrolyte mixture. Moreover, by further blending an electrode active material, it can also be used as an electrode mixture.

[0105] The electrode material may be a positive electrode active material or a negative electrode active material.

[0106] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but for example, a material containing an alkali metal and at least one transition metal is preferable. Specific examples include an alkali metal-containing transition metal complex oxide and an alkali metal-containing transition metal phosphate compound. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal complex oxide that produces high voltage. Examples of the alkali metal ion include lithium ion, sodium ion, potassium ion, etc., and lithium ion is preferable.

[0107] Examples of the alkali metal-containing transition metal composite oxide include: Formula: M a Mn 2-b M 1 b O 4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 c O 2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O 2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), in which M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0108] Among these, MCoO is particularly popular because it can provide secondary batteries with high energy density and high output. 2 , M.M.N.O. 2 , MNiO 2 , M.M.n 2 O 4 , M.N.I. 0.8 Co 0.15 Al 0.05 O 2 , or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 and the like are preferred, and a compound represented by the following general formula is preferred. MNi h Co i Mn j M 5 k O 2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.

[0109] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following general formula: M e M 4 f (PO 4 ) g (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0110] The transition metal of the alkali metal-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, or the like. Specific examples include LiFePO 4 , Li 3 Fe 2 (PO 4 ) 3 , LifeP 2 O 7 Iron phosphates such as LiCoPO 4 and lithium transition metal phosphate compounds in which a part of the transition metal atoms constituting the main part of the lithium transition metal phosphate compounds is replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. As the lithium-containing transition metal phosphate compound, those having an olivine structure are preferable.

[0111] Other examples of the positive electrode active material include lithium-nickel-based composite oxides. The lithium-nickel-based composite oxides are represented by the following general formula: Li y Ni 1-x M x O 2 (wherein x is 0.01≦x≦0.7, y is 0.9≦y≦2.0, and M is a metal atom (excluding Li and Ni)) is preferred.

[0112] Other positive electrode active materials include MFePO 4 , M.N.I. 0.8 Co 0.2 O 2 , M 1.2 Fe 0.4 Mn 0.4 O 2, MNi 0.5 Mn 1.5 O 2 , MV 3 O 6 , M 2 MnO 3 and others can also be mentioned. In particular, M 2 MnO 3 , MNi 0.5 Mn 1.5 O 2 and other cathode active materials are preferable in that the crystal structure does not collapse even when the secondary battery is operated at a voltage exceeding 4.4 V or at a voltage of 4.6 V or higher. Therefore, an electrochemical device such as a secondary battery using a cathode material containing the cathode active material exemplified above is preferable because the remaining capacity hardly decreases, the resistance increase rate hardly changes, and the battery performance does not deteriorate even when operated at a high voltage, even when stored at a high temperature.

[0113] As other cathode active materials, solid solution materials such as M 2 MnO 3 and MM 6 O 2 (where M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 is a transition metal such as Co, Ni, Mn, Fe, etc.) can also be mentioned.

[0114] As the solid solution material, for example, an alkali metal manganese oxide represented by the general formula M x [Mn (1-y) M 7 y O z . Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 consists of at least one metal element other than M and Mn, and contains, for example, one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the ranges of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O 2 such as Li2 MnO 3 Based on LiNiO 2 and LiCoO 2 A manganese-containing solid solution material in which manganese is dissolved is preferable since it can provide an alkali metal ion secondary battery having a high energy density.

[0115] In addition, it is preferable to include lithium phosphate in the positive electrode active material, since the continuous charging characteristics are improved. Although there is no limitation on the use of lithium phosphate, it is preferable to use the positive electrode active material and lithium phosphate mixed together. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, with respect to the total of the positive electrode active material and lithium phosphate, and is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less.

[0116] In addition, a substance having a different composition may be attached to the surface of the positive electrode active material. Examples of the surface-attaching substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0117] The above positive electrode active materials may be used alone or in any combination or ratio of two or more different compositions. In this case, a preferred combination is LiCoO 2 and LiNi 0.33 Co 0.33 Mn 0.33 O 2 Combination with ternary systems such as LiCoO 2 and LiMn 2 O 4 Or a combination of this Mn partially substituted with other transition metals, etc., or LiFePO 4 and LiCoO 2Alternatively, a part of the Co may be replaced with another transition metal or the like.

[0118] The content of the positive electrode active material is preferably 50 to 90% by mass of the positive electrode mixture in terms of high battery capacity. The content in the positive electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit is preferably 88% by mass or less, more preferably 86% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the ion conductivity, electronic conductivity, and electrode strength may be insufficient.

[0119] The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials such as lithium metal, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon; silicon-containing compounds such as silicon and silicon alloys; Li 4 Ti 5 O 12 Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.

[0120] The negative electrode active material used in the present disclosure preferably contains silicon as a constituent element. By using the negative electrode active material containing silicon as a constituent element, a high-capacity battery can be produced.

[0121] The silicon-containing material includes silicon particles, particles having a structure in which silicon particles are dispersed in a silicon-based compound, and silicon-based compounds having the general formula SiO x Silicon oxide particles represented by the formula (0.5≦x≦1.6) or a mixture thereof are preferred. By using these, a negative electrode mixture for a lithium ion secondary battery having a higher initial charge / discharge efficiency, a higher capacity, and excellent cycle characteristics can be obtained.

[0122] In the present disclosure, silicon oxide is a general term for amorphous silicon oxide. Silicon oxide before disproportionation has the general formula SiO x (0.5≦x≦1.6), where x is preferably 0.8≦x<1.6, and more preferably 0.8≦x<1.3. This silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon to produce silicon monoxide gas, and then cooling and precipitating the gas.

[0123] The content of the negative electrode active material is preferably 50 to 90% by mass of the negative electrode mixture in terms of high battery capacity. The content in the negative electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit is preferably 88% by mass or less, more preferably 86% by mass or less. If the content of the negative electrode active material in the negative electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the ion conductivity, electronic conductivity, and electrode strength may be insufficient.

[0124] <Sulfide solid electrolyte layer> The present disclosure also relates to a sulfide solid electrolyte layer using the solid battery mixture of the present disclosure.

[0125] The sulfide solid electrolyte layer of the present disclosure is preferably in the form of a sheet, and the thickness of the sheet is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, even more preferably 180 μm or less, particularly preferably 150 μm or less, and is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.

[0126] In the sulfide solid electrolyte layer of the present disclosure, the content of the fluoropolyether is preferably 0.1 vol% or more, more preferably 1 vol% or more, and is preferably 25 vol% or less, more preferably 10 vol% or less.

[0127] <Electrode layer> The present disclosure also relates to an electrode layer using the solid battery mixture of the present disclosure. The electrode layer of the present disclosure may be a positive electrode layer or a negative electrode layer.

[0128] The electrode layer of the present disclosure is preferably in the form of a sheet, and the thickness of the sheet is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, even more preferably 180 μm or less, particularly preferably 150 μm or less, and is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.

[0129] The electrode layer of the present disclosure is suitably composed of a current collector and an active material layer containing the solid battery mixture of the present disclosure.

[0130] The content of the fluoropolyether in the active material layer is preferably 0.1 vol % or more, more preferably 1 vol % or more, and is preferably 25 vol % or less, more preferably 10 vol % or less.

[0131] When the electrode layer is a positive electrode layer, examples of the material of the current collector include metals such as aluminum, titanium, tantalum, stainless steel, nickel, and the like, and metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among these, metal materials, particularly aluminum or its alloys, are preferred. When the electrode layer is a negative electrode layer, the material of the current collector may be metals such as copper, nickel, titanium, tantalum, stainless steel, or alloys thereof; or carbon materials such as carbon cloth, carbon paper, etc. Among these, metal materials, particularly copper, nickel, or alloys thereof, are preferred.

[0132] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0133] In addition, it is also preferable that the surface of the current collector is coated with a conductive assistant from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver.

[0134] The electrode layer may be produced by a conventional method, for example, a method in which an active material layer and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0135] The density of the active material layer in the positive electrode layer is preferably 2.50 g / cm 3 More preferably, 3.00 g / cm 3 More preferably, 3.20 g / cm 3 or more, and preferably 3.80 g / cm 3 Less than or equal to 3.75 g / cm 3 More preferably, 3.70 g / cm 3 The range is as follows. If the electrolyte content exceeds this range, the ratio of electrolyte to active material will be low, hindering ion conduction to the active material, and the charge / discharge characteristics at high current density will decrease, making it impossible to obtain high output. If the electrolyte content falls below this range, the active material will be insufficient, and the battery capacity may be poor.

[0136] The density of the active material layer in the negative electrode layer is preferably 1.0 g / cm 3 More preferably, 1.2 g / cm 3More preferably, it is 2.5 g / cm 3 Less than or equal to 2.2 g / cm 3 If the electrolyte content exceeds this range, the ratio of electrolyte to active material will be low, hindering ion conduction to the active material, and the charge / discharge characteristics at high current density will decrease, making it impossible to obtain high output. If the electrolyte content falls below this range, the battery capacity may be poor due to a lack of active material.

[0137] <Secondary battery> The present disclosure also relates to a secondary battery comprising the sulfide solid electrolyte layer of the present disclosure and / or the electrode layer of the present disclosure.

[0138] The secondary battery of the present disclosure preferably comprises a positive electrode, a negative electrode, etc., and specifically, a lithium ion secondary battery comprising these is particularly preferred.

[0139] The secondary battery is preferably a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.

[0140] The secondary battery may have any shape, such as a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. The shapes and configurations of the positive electrode, the negative electrode, and the mixture sheet can be changed according to the shape of each battery.

[0141] The solid secondary battery is preferably a lithium ion battery, and is also preferably a sulfide-based all-solid secondary battery.

[0142] The solid secondary battery preferably includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode.

[0143] The solid secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.

[0144] The solid secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, solid electrolyte layer, etc., but specific examples include a cylindrical type, a square type, a coin type, a laminate type, etc.

[0145] The solid secondary battery can be produced, for example, by stacking a positive electrode, a solid electrolyte layer sheet, and a negative electrode in this order and pressing them.

[0146] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0147] Next, the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0148] (Synthesis Example 1: Synthesis of Compound 1-1) In a nitrogen-substituted reaction vessel, 600 mg of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 15.3 mmol), 30 g of 1,3-bis(trifluoromethyl)benzene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 10 g of fluoropolyether both-terminal alcohol (manufactured by Solvay, Fomblin D2, 5.1 mmol) were added and heated and stirred at 70 ° C for 3 hours. The internal temperature was set to 65 ° C, and 5.5 g of triethylene glycol-2-bromoethyl methyl ether (manufactured by Tokyo Chemical Industry Co., Ltd., 20.4 mmol) was dropped from the dropping funnel over 10 minutes, and the mixture was heated and stirred for 6 hours. After returning to room temperature, 5 ml of 1N hydrochloric acid was added to the reaction solution and stirred for 3 hours. This solution was washed four times with pure water, and 2 g of magnesium sulfate was added to the separated organic layer and dried. The volatile matter was removed from the treated solution from which magnesium sulfate had been removed by filtration, and the solution was further dried at 100 ° C for 3 h to obtain the following compound 1-1 (PFPE-PEG). Compound 1-1 was a liquid at 25°C. Compound 1-1: CH 3 O(CH 2 CH 2 O) x1 CH 2 CF 2 (OCF 2 CF 2 ) y (OCF 2 ) z OCF 2 CH 2 O(CH 2 CH 2 O) x2 CH 3 (x1:4, y: average 12.3, z: average 10.2, x2:4, (CH 2 CH 2 O) x1 Number average molecular weight: 176, (CH 2 CH 2 O) x2 Number average molecular weight: 176)

[0149] 1. Preparation of Press Positive Electrode Binder (PVdF), conductive additive (VGCF), and sulfide solid electrolyte (LiI-LiBr-Li 2 SP 2 S5 ) and the positive electrode active material (LiNi 0.80 Co 0.15 Mn 0.05 O 2 ) and optionally compound 1-1 (PFPE-PEG) were added, and the mixture was kneaded using an ultrasonic homogenizer to obtain a positive electrode composite slurry. The obtained positive electrode composite slurry was applied onto an Al foil and dried to obtain a positive electrode for pressing. Here, by changing the amount of PFPE-PEG added, a plurality of positive electrodes for pressing with different volume ratios of PFPE-PEG in the composite were obtained (Examples 1 to 3). The volume ratio of PFPE-PEG in each positive electrode for pressing is as shown in Table 1 below.

[0150] Press positive electrodes (Examples 4 to 6) were prepared in the same manner as in Examples 1 to 3, except that LiTFSI (Kishida Chemical Co., Ltd.) was added to Compound 1-1 so that the salt concentration was 5 mass %.

[0151] Positive electrodes for press use were produced in the same manner as in Examples 1 to 3, except that PFPE-PEG was not used (Comparative Examples 1 to 3).

[0152] 2. Preparation of Pressed Negative Electrode The binder (PVdF), conductive additive (VGCF), and sulfide solid electrolyte (LiI-LiBr-Li 2 SP 2 S 5 ) and the negative electrode active material (Si) were added and mixed using an ultrasonic homogenizer to obtain a negative electrode composite slurry. The obtained negative electrode composite slurry was applied onto a Cu foil and dried to obtain a negative electrode for pressing.

[0153] 3. Preparation of Electrolyte Layer for Pressing The binder (PVdF) and sulfide solid electrolyte (LiI-LiBr-Li 2 SP 2 S 5) was added and mixed using an ultrasonic homogenizer to obtain an electrolyte mixture slurry. The obtained electrolyte mixture slurry was applied onto an Al foil and dried to obtain an electrolyte layer for pressing.

[0154] 4. Battery Preparation The positive electrode, negative electrode and electrolyte layer for pressing were each formed into a rectangular shape, and the composite surface of the positive electrode for pressing and the composite surface of the electrolyte layer for pressing were overlapped, and then roll pressed at 165 ° C. with the pressure shown in Table 1 below, and the Al foil of the electrolyte layer for pressing was peeled off to obtain a laminate (A) of Al foil, positive electrode active material layer and electrolyte layer. On the other hand, the composite surface of the negative electrode for pressing and the composite surface of the electrolyte layer for pressing were overlapped, and then roll pressed at 25 ° C. with a pressure of 30 kN / cm, and the Al foil of the electrolyte layer for pressing was peeled off to obtain a laminate (B) of Cu foil, negative electrode active material layer and electrolyte layer. The laminate (A) was punched out to φ 11.28 mm, and the laminate (B) was punched out to φ 13.00 mm. An electrolyte layer was further transferred to the laminate (B) using a uniaxial press, and the laminate (A) and the laminate (B) were then superimposed to obtain an electrode body having a structure of Al foil / positive electrode active material layer / electrolyte layer / negative electrode active material layer / Cu foil. Current extraction tabs were attached to the Al foil and Cu foil of the electrode body, respectively, and the electrode body was sealed in a laminate pack using a vacuum lami sealer to produce a battery for evaluation.

[0155] 5. Battery resistance evaluation The resistance of the evaluation battery prepared as described above was measured. Specifically, the resistance value of the real axis intercept on the low frequency side of the circular component was read from the Nyquist plot obtained by the AC impedance method, and this was determined as the resistance of the battery.

[0156] 6. Evaluation Results The results are shown in Table 1 below. The configurations and manufacturing conditions of the electrolyte layer and negative electrode are common to the Examples and Comparative Examples, and are therefore omitted from Table 1. The evaluation results of the battery resistance are shown relative to the resistance value in Comparative Example 1 as the reference (100.0). The reduction effects of Examples 1 to 6 show the difference from the results of the Comparative Examples with the same pressing pressure.

[0157] [Table 1]

[0158] The results shown in Table 1 suggest the following: (1) As shown in Comparative Examples 1 to 3, the lower the pressure when molding the positive electrode, the higher the battery resistance. It is considered that the lower the molding pressure, the lower the packing rate of the composite material, resulting in an active material layer with many gaps, and as a result, the battery resistance increases. (2) As shown in Comparative Examples 1 to 3 and Examples 1 to 3, when the pressure during molding of the positive electrode was the same, the battery resistance was smaller when the composite contained PFPE-PEG (Examples 1 to 3) than when the composite did not contain PFPE-PEG (Comparative Examples 1 to 3). Furthermore, in Examples 1 to 3, the increase in resistance when the molding pressure was lowered was suppressed compared to Comparative Examples 1 to 3. In Examples 1 to 3, the lubricating effect of PFPE-PEG increased the fluidity of the composite when molding the positive electrode, and an active material layer with a high filling rate was obtained, which is thought to be the reason for the lower battery resistance. (3) As shown in Examples 4 to 6, the combined use of Compound 1-1 and a lithium salt results in a more significant drag reduction effect, because Compound 1-1 can dissolve the lithium salt.

[0159] In the above embodiment, the fluoropolyether having a specific chemical structure is exemplified, but the chemical structure of the fluoropolyether is not limited to this.Furthermore, in the above embodiment, the case where the fluoropolyether is included in the positive electrode side is exemplified, but the same effect can be expected even when the fluoropolyether is included in the negative electrode side or in the electrolyte layer.In addition, the composite composition of the positive electrode, the electrolyte layer and the negative electrode is not limited to the above.

[0160] As described above, the composition having the following configuration can reduce the resistance of an electrochemical device having a sulfide solid electrolyte. Contains at least one fluoropolyether represented by any one of formulas (1) to (3) and a sulfide solid electrolyte.

Claims

1. At least one fluoropolyether represented by any one of the following formulas (1) to (3), A composition comprising a sulfide solid electrolyte. (1) R1-O-Ra1-Rb1-O-Ra1-R1 (2) R2-Rb2-O-Ra2-Rb2-R2 (3) R3-Rb3-O-Ra3-R3 (In the formula, Ra1 to Ra3 each independently represent a group containing an alkylene unit not containing fluorine and / or an oxyalkylene unit not containing fluorine, The oxyalkylene units of Ra1 to Ra3 are each independently -CHCHO- or -CHCH(J)O-; Each J is independently an alkyl group or an aryl group; Rb1 to Rb3 each independently represent a fluoropolyether group represented by the following formula (4): R1 to R3 are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4) -Rf1-Rf-O-Rf2- (In the formula, Rf1 and Rf2 each independently represent an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

2. The composition according to claim 1, wherein Ra1 to Ra3 are each independently a polyoxyalkylene group represented by the following formula (Ra-I): (Ra-I): -(CH2CH2O)r(CH2CH(CH3)O)s(CH2CH(CH2CH3)O)t(CH2CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

3. The composition according to claim 1 or 2, wherein the number average molecular weights of Ra1 to Ra3 are 40 to 4,000.

4. 3. The composition according to claim 1, wherein each Rf is independently a fluoropolyether group represented by the following formula (Rf-I): Formula (Rf-I): -(OC6F12)a-(OC5F10)b-(OC4F8)c-(OC3Rc6)d-(OC2F4)e-(OCF2)f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer from 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeating unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e and f is 1 or more.

5. The composition according to claim 1 or 2, wherein each Rf is independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): Formula (Rf-II): -(OC3F6)d-(OC2F4)e- (In the formula, d is an integer from 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer from 1 to 200; the sum of c, d, e, and f is 2 or more; The order of the repeating units marked with c, d, e, or f is arbitrary.

6. The composition according to claim 5, wherein each Rf is independently a group represented by formula (Rf-I-II).

7. 3. The composition according to claim 1, wherein R1 to R3 are each independently a methyl group, an ethyl group, a trifluoromethyl group, or a pentafluoroethyl group.

8. The composition according to claim 1 or 2, wherein the sulfide solid electrolyte is LiI-LiBr-Li2S-P2S5.

9. 3. The composition of claim 1, further comprising an alkali metal salt.

10. 10. The composition of claim 9, wherein the alkali metal salt is lithium bis(trifluoromethanesulfonimide).

11. The composition of claim 1 or 2, wherein the fluoropolyether is liquid at any temperature between 25°C and 80°C.

12. The composition according to claim 1 or 2, wherein the content of the polyalkylene oxide represented by the following formula (5) is less than 20 mass %: (5) R1B-(OCHR1A(CH2)jCHR2A)n-OR2B (In the formula, R1A and R2A each independently represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is 0 or an integer from 1 to 2; R1B and R2B each independently represent a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; n is an integer from 5 to 1000.

13. A mixture for a solid-state battery comprising the composition according to claim 1 or 2.

14. The solid-state battery mixture according to claim 13 , further comprising a binder.

15. The solid battery mixture according to claim 13, further comprising a conductive assistant.

16. A sulfide solid electrolyte layer using the mixture for a solid battery according to claim 13.

17. An electrode layer using the solid battery mixture according to claim 13.

18. A secondary battery comprising the sulfide solid electrolyte layer according to claim 16 and the electrode layer according to claim 17.

19. A secondary battery comprising the sulfide solid electrolyte layer according to claim 16.

20. A secondary battery comprising the electrode layer according to claim 17.

21. The electrode layer has an active material layer, 19. The secondary battery in accordance with claim 18, wherein the content of said fluoropolyether in said active material layer is 1 to 25% by volume.

22. The electrode layer has an active material layer, 21. The secondary battery in accordance with claim 20, wherein the content of said fluoropolyether in said active material layer is 1 to 25% by volume.

23. 22. The secondary battery in accordance with claim 21, wherein the content of the fluoropolyether in the active material layer is 1 to 10% by volume.

24. 23. The secondary battery in accordance with claim 22, wherein the content of said fluoropolyether in said active material layer is 1 to 10% by volume.

Citation Information

Patent Citations

  • Non-dehumidifying porous membrane

    JP2012522882A

  • Solid electrolyte slurry, method for manufacturing solid electrolyte sheet, solid electrolyte slurry inclusion body, electrode slurry, method for manufacturing electrode sheet, electrode slurry inclusion body, and method for manufacturing all-solid type lithium ion battery

    JP2016062709A

  • Fluoropolyether group-containing polymer and production method therefor

    WO2020246301A1

  • Solid electrolyte composition

    JP2022506854A